Disinfection Effect of 10% Ricinus Communis Oil on Candida Albicans Counts of Heat Polymerized Acrylic Resin : Pengaruh Desinfeksi Minyak Ricinus Communis 10% terhadap Jumlah Candida Albicans pada Resin Akrilik Polimerisasi Panas - Putri Welda Utami; Nurdiana (TALENTA, 2021)
Dentures is used to replace tooth loss. The most used denture base material is acrylic resin. The biological properties of acrylic resins give microorganisms the ability to colonize. Certain type of microorganism often found at the dentures base is Candida albicans. Denture’s disinfection is usually used to reduce Candida albicans. One of natural source that now is being widely researched is Ricinus communis oil. The purpose of this study was to analyze disinfection effect of Ricinus communis oil 10% on Candida albicans counts on heat polymerized acrylic resin. This research is an experimental laboratory study with a post-test only design. Samples was heat polymerization acrylic resin plates measuring 10 x 10 x 1 mm were made in the Department of Prosthodontic Faculty of Dentistry, Universitas Sumatera Utara with 10 plates for each for 10% Ricinus communis oil group and 0.2% chlorhexidine gluconate group (control). The Candida albicans colonies count was carried out in the Microbiology Laboratory, Faculty of Mathematics and Natural Sciences, Universitas Sumatera Utara using colony counter. The data obtained was statistically count with the Kruskal-Wallis Test. The result showed the decrease in Candida albicans count with the highest value in the 10% Ricinus communis oil group is 9 x 100 CFU/ml and the highest value in the 0.2% chlorhexidine gluconate group is 0 x 100 CFU/ml. The Kruskal-Wallis test showed significant results with p value of 0.0001 (p <0.05) indicating there was a disinfection effect of 10% Ricinus communis oil and 0.2% chlorhexidine gluconate on Candida albicans count of heat polymerized acrylic resin. The study concluded that 10% Ricinus communis oil effective at decreasing Candida albicans count.